First record of the genus Zeuxevania Kieffer, 1902 from Oriental Region (Hymenoptera: Evaniidae) - Li, Yi-Cheng; Xu, Zai-Fu (Zootaxa, 2017)
A new species of Zeuxevania Kieffer, 1902 is described and illustrated from Yunnan, China: Zeuxevania orientalis Li & Xu, sp. nov.. A key to the species of Zeuxevania is provided.